Taking Stock, July 2020 : What Will Be the New Normal for Vietnam? The Economic Impact of COVID-19 - World Bank (World Bank, Hanoi, 2020)
As of early July 2020, life in Hanoi appears to be back to normal or close to what it used to be before the COVID-19 (Coronavirus) pandemic. The government’s policy helped contain the virus and contributed to saving human lives. Today, most social distancing measures have been lifted. However, this rapid return to normality may prove to be illusory. Several economic and financial indicators have not yet bounced back to their precrisis levels, including the gross domestic product (GDP) growth rate that, at 1.8 percent in the first semester of 2020, was approximately 5 percentage points lower than its historical trajectory during recent years. The pandemic has also left indelible scars, especially on people and businesses that were the least prepared for such a shock. A closer look at the streets of Hanoi reveals that some hotels and shops remain closed, while others have simply disappeared. This report argues that Vietnam should not envision a return to the old normal, but rather should define what will be the new normal as the pandemic has changed in so many ways how people live, work, and communicate. The new normal for Vietnam will depend on many factors, but it will be to a large extent shaped by the way the government manages the exit of the COVID-19 pandemic. Because the country will operate in a world with a great deal of domestic and international uncertainty for the foreseeable future, new drivers of growth will be required, including a new role for fiscal policy. Yet, by being ahead of the curve, Vietnam has a unique opportunity to increase its footprint in the world economy and to push ahead with its agenda of reforms so it can accelerate its quest to become a high-income economy in the foreseeable future.